Understanding Women's Empowerment in Developing Kelecung Eco Village as a Tourism Village - Adnyani, Ni Wayan Giri; Ronda, Mirza; Irwanti, Marlinda; Widowati, Dewi (Pancasila International Journal of Applied Social Science, 2024)
The reality highlighted in this study is that there are still disparities experienced by Balinese women amidst their positive contribution in developing tourism. This strengthens the picture of the need for intensive efforts to realize women's empowerment both within the framework of sustainable tourism and sustainable development, especially in newly developing destinations. This study aims to analyze the meaning of women's empowerment in developing Kelecung Eco Village as a tourist village. This research uses an interpretive paradigm and a qualitative approach. The Interpretative Phenomenological Analysis method was used to find the meaning of women's empowerment carried out by actors in developing Kelecung Eco Village as a tourist village. The results of this research show that women's empowerment is interpreted as (1) social balance; (2) community involvement; and (3) sustainability. This study highlights the involvement of women in developing tourism. The findings in this study have practical implications for policy makers at both regional and national levels.